Analysis Of The Implementation Of Flood Pre-Disasters Mitigation Policies In Prodo Village, Pasuruan Regency - Bella Ayu Sherlyta Permata Sari; Sri Wibawani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
High frequency and impact of flooding require systematic management, as outlined in regulations. This study aims to analyze and describe implementation of pre-disaster flood mitigation policies in Prodo Village, Pasuruan Regency. The research method uses qualitative descriptive approach with focus on Smith's implementation theory (Dr. H. Tachjan, 2006): 1. Idealized policy; 2. Target group; 3. Implementing organization; 4. Environmental factors. With Data collection techniques through observation, interviews, documentation. Research results: 1. Implementation of flood mitigation policies is organized with planning and risk analysis. Adequate infrastructure, prevention based on mutual cooperation culture, spatial planning supervision, preparedness training. However, information expansion and coordination are needed 2. RDMA employees, village officials, volunteers, and the main target community build strong public-private partnerships, although attention to vulnerable groups needs to be increased 3. RDMA and village governments play a role in policies, training, and facilities to improve preparedness and self-empowerment 4. Culture of mutual cooperation, social solidarity, agricultural economy, and political aspects support the success of mitigation. The conclusion of this study is: Flood mitigation policy is implemented systematically with ongoing planning, risk reduction, prevention, spatial control, and education. RDMA, village government, volunteers, and community collaborate, forming strong public-private partnerships. RDMA and village officials enhance community preparedness, self-empowerment, program sustainability. Social, economic, cultural, political environment fosters solidarity and shared responsibility, making mitigation a collective effort supported by strong institutional coordination and community participation. has maintained a unity that interacts with each other in the Implementation of Pre-Flood Disaster Mitigation Policy in Prodo Village, Pasuruan Regency.